Complementary food hygiene practice and associated factors among mothers with children aged 6–23 months in Dessie Zuria, South Wollo Zone, Amhara, Ethiopia, 2023 - Addis, Alemayehu Tesfaye; Dawed, Yeshimebet Ali; Yimer, Geleta Mussa; Adem, Yonas Fissha (Frontiers in Nutrition, 2024)
Background Implementing appropriate complementary food hygiene practices is essential to lower the incidence of food-borne disease and malnutrition in children. However, this aspect is often overlooked in resource-limited settings, and information regarding these practices is not fully available and is not assessed enough. Therefore, this study aimed to assess complementary food hygiene practices and their associated factors in Dessie Zuria, South Wollo Zone, Amhara, Ethiopia, in 2023. Methods An institutional-based cross-sectional study design was conducted from 17 April to 18 May 2023, among 366 mothers with children aged 6–23 months. Dessie Zuria was purposively selected, and a systematic random sampling technique was used to recruit study participants. Data were collected using pretested and structured questionnaires. Finally, the data were entered using EPI-info and then exported to SPSS version 26. Bivariable and multivariable logistic regression analyses were used to identify factors associated with complementary feeding hygiene practices. Both crude odds ratios (COR) and adjusted odds ratios (AOR) with a 95% confidence level (CI) were computed, and a p-value of <0.05, in the final model, was considered statistically significant. Results The proportion of households practicing complementary food hygiene was 22.22%. Factors associated with these practices included access to media such as television or radio (AOR = 10.51, 95% CI: 2.8, 39.28), starting complementary feeding before 6 months (AOR = 2.01, 95% CI: 1.05, 3.84), and the child’s age being 6 to 11 months (AOR = 0.25, 95% CI: 0.08, 0.7). Conclusion The prevalence of complementary food hygiene practices was poor. Healthcare professionals should promote starting breastfeeding at the age of 6 months. In addition, media companies ought to make an effort to create a positive social and cultural environment that encourages complementary feeding practices for young children.